TINJAUAN HUKUM ISLAM TERHADAP IMPLEMENTASI AKAD MUSHARAKAH MUTANAQISAH SEBAGAI SOLUSI AKAD PEMBIAYAAN KREDIT PEMILIKAN RUMAH PADA BANK SYARI’AH - M. Taufiqurrosyidin Abdillah (Maliyah : Jurnal Hukum Bisnis Islam, 2015)
Musharakah mutanaqisah contract is a form of contract solutions murabahah formerly used as a mortgage financing agreement with Bank Muamalat Indonesia.The implementation of the contract musharakah mutanaqisah on mortgage financing product is a form of cooperation partnerships undertaken by the bank and the customer in the housing where the bank contributes funds to customers based on mutual agreement. Whereas ijarah contract is an aggrement which is obligated to client to pay a number of rent payment which was given by side of bank as the service because it has become the object of utilizing home mortgage financing is accompanied by the transfer of ownership of the house at the end of the full payment. Thus, the study of Islamic law in the implementation of the contract musharakah mutanaqisah has met its validity, because its pillars and conditions have been met.